Microplastic in the Aquatic Ecosystem and Human Health Implications - Ojha A.; Mishra A.; Tiwary D. (My University, 2025)
xOver the past few decades plastic pollution has become a matter of grave concern, and combatting it has been challenging for environmentalists. Massive dumping of plastic wastes has undoubtedly created a threatening situation for aquatic ecosystems and human health. Microplastics (MPs) are defined as plastic fragments with a size <5â€‰mm in length that tend to stay in marine and freshwater systems. Their concentration varies from location to location, and so does their effect on human health. The capturing of these MPs has created a significant issue in the aquatic fauna. Their engulfment or entanglement by freshwater and marine animals makes their entry into the human food chain a certainty. Entering these MPs into the human system can create significant health impacts such as neural, renal, hepatic, and congenital disorders. They are not only harmful as such, but are known to be a potent carrier for many organic and inorganic pollutants. This chapter focuses on the rising impact of these MPs on human health and considers various organ systems that are affected by them. Some of the case studies and plausible solutions will also be considered while discussing these environmental hazards. © 2022 John Wiley & Sons Ltd. All rights reserved.